2019
DOI: 10.17719/jisr.2019.3171
|View full text |Cite
|
Sign up to set email alerts
|

Türki̇ye De Mobbi̇ng Konusunda Yapilan Tez Çalişmalari: Meta Anali̇zi̇

Abstract: ÖzMobbing, son dönemlerde çok fazla gündemde olan bir konudur. Sosyal bilimlerde insanla ilişkili olan her konu önem arz etmektedir. Mobbing konusu da sıklıkla çalışma hayatında karşımıza çıkan önemli bir sosyal olgudur. Bu çalışmada mobbing konusunda üretilen tez çalışmalarının meta analizi yapılmıştır. Bir meta analizi olan bu çalışmada 2005 yılından itibaren üretilen YÖK Ulusal Tez Merkezi'ndeki tezlerin tamamı ele alınmış olup bilim alanları ve alt dallarına göre frekans analizi yapılmıştır. ULusal Tez Mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Mobbing is one of the subjects that has been extensively studied in our country and the world. Yorulmaz (2019), in his meta-analysis study conducted within the scope of including mobbing in thesis studies in Turkey, revealed that this concept had been studied in many fields, such as economic, administrative sciences, medicine, sociology, psychology, and sports sciences. In their meta-analysis study, Jiménez & Lai (2015) concluded that the characteristics of mobbing perpetrators and mobbing victims and the effects of mobbing on the victims and the organization had been extensively researched.…”
Section: Action Focusmentioning
confidence: 99%
“…Mobbing is one of the subjects that has been extensively studied in our country and the world. Yorulmaz (2019), in his meta-analysis study conducted within the scope of including mobbing in thesis studies in Turkey, revealed that this concept had been studied in many fields, such as economic, administrative sciences, medicine, sociology, psychology, and sports sciences. In their meta-analysis study, Jiménez & Lai (2015) concluded that the characteristics of mobbing perpetrators and mobbing victims and the effects of mobbing on the victims and the organization had been extensively researched.…”
Section: Action Focusmentioning
confidence: 99%
“…Mobbing is one of the subjects that has been extensively studied in our country and the world. Yorulmaz (2019), in his meta-analysis study conducted within the scope of including mobbing in thesis studies in Turkey, revealed that this concept had been studied in many fields, such as economic, administrative sciences, medicine, sociology, psychology, and sports sciences. In their meta-analysis study, Jiménez & Lai (2015) concluded that the characteristics of mobbing perpetrators and mobbing victims and the effects of mobbing on the victims and the organization had been extensively researched.…”
Section: Action Focusmentioning
confidence: 99%
“…Çalışma arkadaşlarının ya da idarenin bu zorbanın tutumunu iyileştirmedeki eksikliği veya buna dayanması sonucu zorba, güçlenmekle birlikte çevresindeki kişiler de söz konusu bu yıldırmaya ortaklık etme sürecine girmektedirler (Altuntaş, 2010: 3000). (Yorulmaz, 2019(Yorulmaz, : 1637.…”
Section: İş Yaşamında Psikolojik Tacizunclassified